Theology of Revolution: In Ali Shari’ati and Walter Benjamin’s Political Thought - Khanlarzadeh, Mina (Religions, 2020)
In this paper, I offer a comparative analysis of the political thoughts of twentieth century Iranian revolutionary thinker and sociologist Ali Shari’ati (1933-1977) and German-Jewish philosopher Walter Benjamin (1892-1940). Despite their conspicuously independent historical-theoretical trajectories, both Shari’ati and Benjamin engaged with theology and Marxism to create theological-political conceptions of the revolution of the oppressed. Shari’ati re-interpreted and re-animated Shia history from the angle of contemporary concerns to theorize a revolution against all forms of domination. In comparison, Benjamin fused Marxism with Jewish theology in his call to seize the possibilities of past failed revolutions in the present. Both Shari’ati and Benjamin conceptualized an active messianism led by each generation, eliminating the wait for the return of a messiah. As a result, each present moment takes on a messianic potential; the present plays an essential role to both thinkers. Past was also essential to both, because theology (through remembrance) had made the past sufferings incomplete to them. Both thinkers viewed past sufferings as an integral part of present struggles for justice in the form of remembrance (or yād or zekr for Shari’ati, and Zekher for Benjamin). I explore the ways Shari’ati and Benjamin theorized the role of the past in the present, remembrance, and messianism to create a dialectical relation between theology and Marxism to reciprocally transform and compliment both of them.